Impact of Positive Organizational Behavior on Self-Efficacy in Improving The Quality of Work of PT Kareta Sabila Employees - Indri Guslina (Eduvest - Journal of Universal Studies, 2023)
Positive Organizational Behavior has a wide reach, from the organization's past buried in by business ideology, through the present with urgent needs and emerging opportunities. This qualitative study aims to find out positive organizational behavior on self-efficacy. Positive Organizational Behavior is not just explicit knowledge, skills, and abilities that can only be built through educational and training programs, or even through work experience. Positive Organizational Behavior is also not equivalent to organization-specific tacit knowledge built by managers and employees over time by taking time and immersing themselves in the socialization process to build motivation in improving the quality of employee work. Positive Organizational Behavior also brings new and exciting opportunities above and above that are provided by social relationships and networks across individuals, departments, and organizations. Positive Organizational Behavior has triggered a paradigm shift far from just a negative emphasis on pathology that fills handbooks, dictionaries and classification systems of clinical psychologists. Similarly, Positive organizational behaviour offers organizational behaviour and human resource management researchers and practitioners a new positive perspective, far from the 'gloom and doom' focusing on dysfunctional employees, aggression in the workplace, incompetent leaders, stress and conflict, unethical behaviour, ineffective strategies and counterproductive organizational structures and cultures